2014
DOI: 10.1055/s-0033-1363232
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Imaging of Pancreatic Islet Transplantation

Abstract: Islet replacement therapy, pancreatic islet transplantation, is considered as a potential option for curing T1DM. However, the significant loss of implanted islets after islet transplantation prevents it from becoming a mainstream treatment modality. Due to the lack of reliable noninvasive real-time imaging techniques to track the survival of the islets, it is impossible to discover the specific causes for the loss of implanted islets, not to mention taking interventions in the early stage. Current achievement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
0
5
0
1
Order By: Relevance
“…Fourth, many factors may cause loss of SPIO signal in transplanted islet cells, eg, immune rejection, ischemia and inflammation in the liver after islets transplantation. 6,13,14 SPIO-labeled islets are more suitable for real-time imaging of transplanted islets. 15 Although Resovist is approved for clinical use as a liver-imaging agent 16 and it has been proved that porcine islets can safely and efficiently be labeled with Resovist to monitor kidney capsules of diabetic mice ( Figure 1A), 17 it has not been applied further because of its instability in clinical trials.…”
Section: Superparamagnetic Iron Oxide (Spio)mentioning
confidence: 99%
See 2 more Smart Citations
“…Fourth, many factors may cause loss of SPIO signal in transplanted islet cells, eg, immune rejection, ischemia and inflammation in the liver after islets transplantation. 6,13,14 SPIO-labeled islets are more suitable for real-time imaging of transplanted islets. 15 Although Resovist is approved for clinical use as a liver-imaging agent 16 and it has been proved that porcine islets can safely and efficiently be labeled with Resovist to monitor kidney capsules of diabetic mice ( Figure 1A), 17 it has not been applied further because of its instability in clinical trials.…”
Section: Superparamagnetic Iron Oxide (Spio)mentioning
confidence: 99%
“…Fourth, many factors may cause loss of SPIO signal in transplanted islet cells, eg, immune rejection, ischemia and inflammation in the liver after islets transplantation. 6 , 13 , 14 SPIO-labeled islets are more suitable for real-time imaging of transplanted islets. 15 …”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
See 1 more Smart Citation
“…С помощью позитронно-эмиссионной томографии установлено, что сразу после внутрипортального введения 50-70% островков теряет жизнеспособность. Поэтому необходимо использование взвеси от 2-3 доноров [25,26].…”
Section: реакция островков на имплантациюunclassified
“…In the last few years, islet transplantation has arisen as a treatment alternative for T1DM. To visualize transplanted islets and monitor their fate, various noninvasive probes and functionalized nanoparticles have been investigated and significant success has been achieved in basic trials to date [171][172][173]. The first successful in vivo imaging and detection of transplanted islets was reported by Lu et al in 2004, wherein the authors transfected islets with a recombinant adenovirus coding for the luciferase gene and demonstrated that introduction of reporter gene-directed luciferase expression into the isolated islets allowed the long-term monitoring of grafted islets [174].…”
Section: Optical/spect/pet Probesmentioning
confidence: 99%